HIGH-PRODUCTIVITY TECHNOLOGY OF SHALLOW ELECTROMAGNETIC MAPPING - Karin, Yu.G.; Balkov, E.V.; Pozdnyakova, O.A.; Shaparenko, I.O.; Panin, G.L.; Fadeev, D.I. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2024)
In the paper, equipment for shallow electromagnetic mapping Geoviser, the design and dimensions of special non-magnetic sledges, as well as the features of their use in the field, in combination with a high-precision positioning system are described. Based on the results of the study of archaeological sites of various types (fortified settlement, burial mound), and their comparison with the data of other remote sensing methods, conclusions were made about the efficiency of the used technology: equipment and approaches to its application. A significant increase in the productivity of electromagnetic mapping is shown, while maintaining high data density, opening up prospects for the widespread implementation of the proposed method as the first stage of studying the geoelectric properties of the environment. In the study of archaeological sites, electromagnetic mapping significantly complements aerial photography data, allowing to identify objects that are not expressed in the relief. Successful testing of the described technology on archaeological sites of the Novosibirsk Region demonstrates the need for its implementation in such areas as archeology, engineering and environmental geophysics, precision agriculture.